Conceptos clave de la gestión cultural Enfoques desde Latinoamérica Volumen I - Chavarría Contreras , Rafael; Fauré Polloni, Daniel; Mariscal Orozco, José Luis; Rucker, Ursula; Yáñez Canal, Carlos (b1bea1c2-cc6a-4934-b727-ba9040daaeb3, 2018)
In this first volume, this book proposes concepts about culture and its location in the social and academic life of our region